Efectos espaciales en la formación de precios de oferta en mercados spot de generación eléctrica (2016)
The price bid mechanism in the Colombian electricity market exhibits a strategic behavior, inherent in their oligopolistic market structure, not only for its high hydrological percentage, about 80%, but also because the power plants geographical location, near to the Andean Region. This research designs a spatial weights matrix reflecting characteristics the power plants geographical location, who is incorporated into a spatial Durbin panel to identify the economic geography behaviors, in addition to the fundamentals that explain the prices formation in this market.